2. Dydrogesterone-primed ovarian stimulation versus gnrh antagonist protocol in in-vitro fertilization for poor responders: A pilot study - Thach, Than Trong; Ha, Nguyen Manh; Hoang, Le (Tạp chí Nghiên cứu Y học, 2024)
PPOS (Progestin-Primed Ovarian Stimulation) has shown efficacy in preventing early luteinization and improving outcomes in infertile women. However, data among those with poor ovarian response (POR) are limited. This study aimed to evaluate the effect of PPOS protocol on the chance of success throughout the IVF process in patients with POR (POSEIDON group III & IV) undergoing IVF/ICSI in Vietnam. This was a randomized controlled trial involving 120 infertile women with POR. PPOS or GnRH-ant protocol was randomly applied to the participants of either group (n = 60 in each group). The primary outcome measures the chances of achieving oocyte maturation and retrieval, fertilization, and embryo formation. The effect of PPOS compared to GnRH-ant protocol was estimated as marginal risk-ratio (RR) from binomial regression analysis. We found that the chance of success in achieving MII oocytes, fertilization, and high-quality D3 and D5 embryos were equivalent between the two protocols; (RR (95% CI) were 0.97 (0.88-1.07), 1.00 (0.89-1.14), 1.04 (0.96-1.14), 1.14 (0.74-1.73), respectively). In conclusion, PPOS protocol using DYG slightly improves the IVF funnel in women with POR undergoing IVF/ICSI; however, these differences were not significant. Therefore, we concluded that the efficacy of the PPOS protocol is equivalent to that of the GnRH-ant stimulation protocol. Clinical Trial Registration Number: NCT06191809